Can cell-cultured meat from stem cells pave the way for sustainable alternative protein? - Octavio Bignardi da Silva Nunes; Tiago Willian Buranello; Fabiana de Andrade Farias; Jenyffer Rosero; Kaiana Recchia; Fabiana Fernandes Bressan (Current Research in Food Science)
As the global population grows, the demand for food and animal-derived products rises significantly, posing a notable challenge to the progress of society in general. Alternative protein production may adequately address such a challenge, and cell-based meat production emerges as a promising solution. This review investigates methodologies for in vitro myogenesis and adipogenesis from stem cells (adult, embryonic, or induced pluripotent stem cells - iPSCs) across different animal species, as well as the remaining challenges for scalability, the possibility of genetic modification, along with safety concerns regarding the commercialization of cell-cultured meat. Regarding such complexities, interdisciplinary approaches will be vital for assessing the potential of cell-cultured meat as a sustainable protein source, mimicking the sensory and nutritional attributes of conventional livestock meat whilst meeting the demands of a growing global population while mitigating environmental impacts.